2023
DOI: 10.3390/microorganisms11071663
|View full text |Cite
|
Sign up to set email alerts
|

On the Negative Impact of Mycorrhiza Application on Maize Plants (Zea mays) Amended with Mineral and Organic Fertilizer

Abstract: Many studies describe the positive effect of mycorrhiza, but few report on negative effects. Furthermore, there is a research gap on the mechanisms under which conditions the symbiotic mycorrhizal plant interaction or a parasitic one predominates. The study was conducted as a field experiment over three years to investigate the effect of mycorrhiza (Rhizoglomus intraradices) and soil bacteria applications on fertile soil. A standard fertilizer (diammonium phosphate) and two microgranular fertilizers (mineral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…According to one study, using a microbial consortium made up of Xanthobacter autotrophicus, Saccharomyces cerevisiae, Schizosaccharomyces pombe, and Pichia norvegensis with 70% NH4NO3 fertilizer improved the phenology, biomass, and germination of Zea mays (Velazquez-Medina et al, 2023). Research conducted on the impact of mycorrhiza (Rhizoglomus intraradices) and soil bacteria applications on maize production revealed that the concurrent usage of soil bacteria mitigated the adverse effects of mycorrhiza treatment (Thielicke et al, 2023). Furthermore, adding organic chicken manure fertilizer and inoculating maize plants with Funneliformis mosseae (FM) enhanced the nitrogen content and photosynthetic efficiency, indicating the possibility of utilizing FM and organic fertilizers to boost maize development (Yooyongwech et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to one study, using a microbial consortium made up of Xanthobacter autotrophicus, Saccharomyces cerevisiae, Schizosaccharomyces pombe, and Pichia norvegensis with 70% NH4NO3 fertilizer improved the phenology, biomass, and germination of Zea mays (Velazquez-Medina et al, 2023). Research conducted on the impact of mycorrhiza (Rhizoglomus intraradices) and soil bacteria applications on maize production revealed that the concurrent usage of soil bacteria mitigated the adverse effects of mycorrhiza treatment (Thielicke et al, 2023). Furthermore, adding organic chicken manure fertilizer and inoculating maize plants with Funneliformis mosseae (FM) enhanced the nitrogen content and photosynthetic efficiency, indicating the possibility of utilizing FM and organic fertilizers to boost maize development (Yooyongwech et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They have been shown to increase the yield and root density of young maize plants in pot experiments [13,14]. Two field studies have found maize yields after MG starter fertilization to be about equal to yields with standard diammonium phosphate (DAP) starter fertilization [15,16]. The widespread usage of MG as a starter fertilizer in maize could simultaneously lower nutrient inputs and be a step towards closing nutrient cycles.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies investigating the agronomic potential of MG as a starter fertilizer in the field. Also, there are very few studies using in-furrow inoculation with AMF and PGPR [15,16,49,50] as a replacement for starter fertilization. Little is known about the impact of AMF and PGPR inoculation on the native soil microbial community [41], although it plays a pivotal role in nutrient cycles and is an important factor in soil quality.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation agriculture practices, including ploughless soil cultivation methods and localised starter fertilisation, must be well-suited to the local conditions to provide the beneficial production and environmental effects hoped of them. This is because their incorrect use can negatively affect the soil properties and plant yields [46][47][48]. The ambiguity of results published in past scientific works, the changing habitat conditions of field plant production, and the technical and technological advances in soil cultivation and plant fertilisation all justify further scientific research in this area.…”
Section: Introductionmentioning
confidence: 99%